Indexing is not merely a badge; it is a bridge connecting local insights to global solutions: experience from six years of editorial process - Amgain, Kapil (Journal of Karnali Academy of Health Sciences, 2025)
This editorial chronicle the systematic indexing trajectory of the Journal of Karnali Academy of Health Sciences (JKAHS) from 2018–2025. As the first premier diamond open-access health sciences journal of Karnali Province of Nepal, JKAHS achieved sequential integration into six major indexing platforms: Google Scholar (2019), Nepal Journals Online (NepJOL, 2020), Index Copernicus (2020), J-Gate and JournalTOCs (2021), Crossref (2022), Directory of Open Access Journals (DOAJ, 2024), and HINARI (2024). Each platform has contributed uniquely—improving discoverability, regional outreach, metadata interoperability, open‐access credibility, and equitable access for resource‐limited settings—thereby reinforcing JKAHS’s mission to disseminate high‐impact biomedical research. The indexing milestone is analyzed for its technical requirements, strategic value, and impact on the journal’s global visibility, academic credibility, and alignment with institutional mandates for equitable knowledge dissemination. Data demonstrate increase in submissions and citation growth post-indexing. The journal’s archiving infrastructure and zero-fee publishing model are highlighted as critical enablers. Challenges in sustaining indexing compliance and future pathways toward Scopus, Web of Science and MED- LINE/PubMed inclusion are also discussed. This article reflects on our indexing journey from Google Scholar to Hinari, shedding light on the challenges, strategies, and outcomes of this transformative process. Keywords: Scholarly indexing, open access, academic publishing, academic visibility, academic integrity